Pineapple leaf juice characterization and kinetic study on microbial growth inhibition - Amirah, Ya'acob; Norazwina, Zainol; Kamaliah, Abdul Samad (Penerbit UTM Press, 2022)
Microbial growth inhibitor (MGI) is crucial in preventing the spreaders of infection. Pineapple (Ananas comosus) leaf juice (PLJ) is chosen as an alternative MGI agent due to its phenolic compounds content. Phenolic compounds in PLJ were quantified by ultra-high performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC-QTOF-MS) analysis. Phenolic compounds identified were confirmed based on their molecular mass and fragmentation pattern. From PLJ characterization, seven phenolic compounds were identified, namely meliadanoside A, feralolide, kukoamine A, methyl-5-O-caffeoylquinate, stilbostemin D, octahydrocurcumin and agrimol C. As the time increased from 0 to 60 min, the phenolic compounds concentration-absorbance (Au) value decreased, indicating a decrease in the phenolic concentration. This is due to the inhibition of microbes by phenolic compounds in PLJ. The inhibition data obtained in microbial inhibition assay were plotted according to the Hill equation, where the kinetic constants (Vmax, K0.5, and n) were estimated. Meliadanoside A has the highest K0.5 value followed by feralolide, kukoamine A, methyl-5-O-caffeoylquinate, and stilbostemin D. Meliadanoside A displayed a sigmoidal behaviour with a Hill coefficient (n) greater than 1. Feralolide, kukoamine A, methyl-5-O-caffeoylquinate, and stilbostemin D corresponded to negative cooperativity with n values lower than 1. This study demonstrated that PLJ could be exploited as a natural plant source that acts as an effective microbial growth inhibitor. Thus, it becomes one of the greener alternatives MGI compared to other synthetic agents.